Study on Single Dose Preoperative Antibiotic Prophylaxis versus Routine Long Term Postoperative Prophylaxis in Elective General Surgical Cases - Chandra Sekhar Chevuturu (Asian Journal of Medical Research, 2019)
Background: The preventive effect of the routine use of preoperative surgical antibiotic prophylaxis (SAP) on the occurrence of surgical site infections (SSI) prior to non-clean and implant surgery has long been recognized. Subjects and Methods: A total of 100 patients were included in the study and divided in to Group A and Group B. Group A contains patients with 1 g of cefotaxime sodium intravenously, that is, single dose was given 1 h before induction of anesthesia and Group B contains patients who were given first dose at 1 h before induction of anesthesia, and subsequent doses were given at an interval of 12 h after surgery for 5 days, that is, multiple dose. Results: This case comparative study were conducted in 100 cases, out of which 50 was included in Group A & 50 was included in Group B. In group A & B different surgical procedure have been done during the study period which is shown in table 1. In group A & B hernioplasty was done in 28% of total cases followed by other procedure. Conclusion: In can be concluded that single preoperative dose of cefotaxime sodium is cost-effective and is as effective as multiple-dose prophylaxis. In elective general surgical cases, it is a reliable method of prophylaxis.